2012
DOI: 10.1016/j.jaad.2011.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer risk perceptions: A comparison across ethnicity, age, education, gender, and income

Abstract: Background Studies of non-cutaneous and cutaneous malignancies support the hypothesis that poor risk-perception status contributes to health disparity. Objective We evaluated skin cancer risk perceptions across race and other demographic markers using the Health Information National Trends Survey (HINTS) and compared them to discover differences in perception that may contribute to the disparities in skin cancer diagnosis and treatment. Methods Respondents with no prior history of skin cancer were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 57 publications
5
94
0
2
Order By: Relevance
“…This is because tan skin is found not only in caucasian populations but also in individuals of Asian, Hispanic, African and Afro-American descent, some of whom perceive themselves to be at a lower risk for developing sunburn or skin cancers. 35,36 However, sunburn has been reported among Hispanic black, Asian/Pacific islanders and American Indians/Alaska natives. 37 Furthermore, even though skin cancers are less frequent in nonwhite/darkly pigmented individuals, it is often associated with increased morbidity and mortality due to a lack of awareness of these diseases among these populations, associated with a delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is because tan skin is found not only in caucasian populations but also in individuals of Asian, Hispanic, African and Afro-American descent, some of whom perceive themselves to be at a lower risk for developing sunburn or skin cancers. 35,36 However, sunburn has been reported among Hispanic black, Asian/Pacific islanders and American Indians/Alaska natives. 37 Furthermore, even though skin cancers are less frequent in nonwhite/darkly pigmented individuals, it is often associated with increased morbidity and mortality due to a lack of awareness of these diseases among these populations, associated with a delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Buster et al 37 found that people who were less educated, elderly, or black were more likely to perceive themselves as being at low risk for developing skin cancer and were less inclined to receive skin examinations. In their survey of more than 500 patients who survived cutaneous melanoma, Pollitt et al 5 found that lower levels of education were associated with decreased perception and knowledge of risk for cutaneous melanoma.…”
Section: Barriers Related To Povertymentioning
confidence: 99%
“…37,5658 Blacks 37,50,59 and Hispanics 5962 perceive themselves to be at very low risk for developing skin cancer. A study by Pichon et al 50 observed no difference in sunscreen use among blacks who reported they perceived a high risk of skin cancer versus those who perceived no risk of skin cancer.…”
Section: Barriers Related To Culturementioning
confidence: 99%
“…This may stem from lower levels of perceived skin cancer risk among SFGH participants, diff erences in access to primary care and dermatologic follow-up, or decreased skin cancer education by health care providers, compared with Diller participants. 40,41 In addition to the disparities we observed in cancer screening practices, we also note diff erences between hospitals in breast cancer detection and treatment. Although lump palpation was the most frequent method of detection at both hospitals, mammographically detected breast cancer was more common at Diller compared with SFGH.…”
Section: Discussionmentioning
confidence: 70%